Remote advanced lab course: A case study analysis of open-ended projects - Jessica R. Hoehn (American Physical Society, 2021)
The rapid transition to remote teaching in the spring of 2020 posed particular challenges for laboratory courses, which often involve students working hands-on with equipment in collaborative environments. Replicating in-person experiments was especially challenging for advanced lab courses that utilize specialized apparatus, which could not be accessed by students at home. However, physics lab instructors employed a variety of creative strategies to overcome these barriers and provide students access to lab-like learning in a remote setting. We report on one advanced lab course that used the transition to remote teaching to completely redefine the course goals and transition from traditional prescriptive labs to more open-ended projects. We conduct a case study analysis, triangulating among several data sources—survey responses and interviews from both instructor and students—to construct an in-depth understanding of the remote course and how students experienced it. Although we cannot necessarily generalize the results of this analysis to the entire student experience in the course due to the student response rate, the feedback that the course did receive from both students and the instructor was overwhelmingly positive, and the instructors are planning to retain the open-ended projects when the course returns to an in-person format. We find that the new open-ended projects afforded students opportunities to make decisions and think deeply about their experiments, which students report as contributing to their enjoyment and satisfaction with the course. Students had mixed group work experiences, with some describing positive and meaningful interactions and others describing group work as a source of frustration and stress. Additionally, some students missed being able to work hands-on with equipment, and some reported a high workload that made the course stressful. We discuss these student experiences and provide implications for both in-person and remote lab courses.